A study on the effect of low-cost eggshell reinforcement on the immersion, damping and mechanical properties of magnesium–zinc alloy. (1st February 2020) - Parande, Gururaj; Manakari, Vyasaraj; Sharma Kopparthy, Sripathi Dev; Gupta, Manoj
Abstract: The requirement for lightweight inexpensive materials with superior performance has been increasing rapidly in the last decade due to the enforcement of stringent environmental protocols and severe in-service conditions in a global effort to mitigate the effect of greenhouse gas emissions. Thereby, the interest in using naturally available materials with minimum processing or handling costs has been explored in the light metal community. Economically Conscious Magnesium (ECo–Mg) composites are one such domain catering to these needs by using naturally available low-cost reinforcements to develop high-performance composites. In this study, the authors have attempted to reinforce eggshell (ES) particles in varying amounts (3, 5 and 7 wt %) to develop magnesium-(2.5 wt %) zinc-based composites using energy-efficient disintegrated melt deposition technique. The reported results reveal a superior enhancement in grain refining ability, damping and mechanical properties of Mg–Zn alloy with the incorporation of eggshell without increasing the density drastically. In particular, Mg-2.5Zn-5ES composite exhibits superior corrosion resistance compared to the Mg-2.5Zn due to the formation of bioactive apatite layer. In the current work, an attempt is made, to study the post corrosion mechanical properties to understand the extent of strength retention of the composites. The results revealed in the current study are benchmarked against commercial metallic implants and biocompatible alloys/composites for better insight into the discussed properties.